1995
DOI: 10.1063/1.360468
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of amorphous and microcrystalline silicon films deposited by low-pressure chemical vapor deposition

Abstract: In this work we used Raman spectroscopy to investigate the structural characteristics of as-deposited amorphous and micro-crystalline silicon films. For amorphous silicon films, the order (or disorder) of the silicon network was quantified using properties of the Raman spectra that were related to key deposition conditions. We found that a strong relationship exists between the structural order of the silicon matrix and the deposition temperature and deposition rate. A quantitative model was proposed relating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(125 citation statements)
references
References 16 publications
10
113
0
2
Order By: Relevance
“…The broad shoulder near the nanocrystal Si peak of 513.5 cm −1 can be observed. As shown in Figure 1(b), we have deconvoluted the spectrum to obtain the peak centered at a wavenumber of 513.5 cm −1 which belongs to the nanocrystal Si, and four broad peaks which are the characteristic peaks of amorphous silicon at wavenumber of 480 cm −1 (transverse optical mode), 380 cm −1 (longitudinal optical mode), 301 cm −1 (longitudinal acoustic mode), and 150 cm −1 (transverse acoustic mode) [34][35][36][37][38][39]. The Raman spectrum analysis has revealed that nanostructured silicon and amorphous silicon were generated simultaneously during the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The broad shoulder near the nanocrystal Si peak of 513.5 cm −1 can be observed. As shown in Figure 1(b), we have deconvoluted the spectrum to obtain the peak centered at a wavenumber of 513.5 cm −1 which belongs to the nanocrystal Si, and four broad peaks which are the characteristic peaks of amorphous silicon at wavenumber of 480 cm −1 (transverse optical mode), 380 cm −1 (longitudinal optical mode), 301 cm −1 (longitudinal acoustic mode), and 150 cm −1 (transverse acoustic mode) [34][35][36][37][38][39]. The Raman spectrum analysis has revealed that nanostructured silicon and amorphous silicon were generated simultaneously during the laser irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…The microcrystalline Raman spectra were fit to a sum of two Lorentzian peaks corresponding to the crystalline and amorphous phases. This allows us to calculate the crystalline volume fraction (x c ) from a ratio of the integrated peak intensities and average distance between point defects (l d ) from the full-width half maximum (FWHM) of the crystalline peak [13][14][15]. The apparatus used to gather the Raman spectra is composed of an Argon ion laser with a wavelength of 514.5 nm with a power of 300 mW, collection optics, 0.6 m triple monochromator, and a cooled CCD camera.…”
Section: Methodsmentioning
confidence: 99%
“…The crystalline fraction F c in a material has sometimes been estimated by integrating the peak intensity associated with the amorphous and crystalline phases, I a and I c respectively [27]:…”
mentioning
confidence: 99%